Demokrasi religius : pemikiran politik Nurcholish Madjid dan M. Amien Rais - Thaha, Idris, 1966- (Jakarta : Teraju ; Bandung : Didistribusikan oleh Mizan Media Utama, 2005)
Islam and democratic system in Indonesia; comparative analysis and political thoughts of Nurcholish Madjid and Amien Rais
Daftar bacaan : p. 321-341
Keywords: Rais, M. Amien; Majid Nurcholish, -- 1939-; Politician -- Indonesia; Islam and politics -- Indonesia; Indonesia -- Politics and government